(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Water shortages in the Republic of Karakalpakstan, the lack of equal access to all water-consuming areas, the reconstruction and expansion of roads and railways, the premature death of old trees, and other factors have led to the need to bring unused arable land into circulation in Karakalpakstan. The article presents data on the yield of agricultural crops obtained on the control variant of land without reclamation and after its implementation, the effectiveness of various methods of maintaining soil fertility during reclamation, their impact on soil fertility, and the economic efficiency of reclamation work.